TOKSISITAS LIMBAH CAIR MINYAK BUMI TERHADAP BENIH KERAPU BEBEK (Cromileptis altivelis) - ', Syafriadiman; Huri, Eryan; Harahap, Sampe (Fakultas Perikanan dan Kelautan, Universitas Riau, 2009)
Acute toxicity and sub-acute test of heavy metal Cd (cadmium) to fish ofcath-fish (Cromileptes altivelis) have been done from January 10th-March 20th2009 in Laboratory of Water Quality Management, Faculty of Fisheries andMarine Science, Riau University, Pekanbaru. This experiment aimed to determinethe lethal and sub-acute toxicities of the heavy metal Cd (cadmium) toxicantconcentration to fish of the cath-fish, Cromileptes altivelis, which is an importantof fish species freshwater culture in Indonesia, especially in Riau. Result of theexperiments indicated that heavy metal Cd (cadmium) concentrations have aneffect on to mortalitas, absolute weight growth, daily growth rate, survival rateand behavior of Cromileptes altivelis). LC50 96 value was 1,295 mg/L. And AF(Application factor) value is 0,01. Evaluation on the safe concentration level ofthe heavy metal Cd (cadmium) toxicant was based on the data obtained fromsubchronic tests (i.e. effects on the absolute weight growth, daily growth rate,survival rate and behaviour). The estimate values of NOEC (No Observed EffectConcentration) for heavy metal Cd (cadmium) toxicant was 0,013 mg/L.